2002
DOI: 10.1093/bja/88.5.708
|View full text |Cite
|
Sign up to set email alerts
|

High-frequency oscillation in adolescents

Abstract: We found HFO, in conjunction with manual recruitment and prone positioning, to be a well-tolerated mode of ventilation in adolescents with ARDS and who were unresponsive to conventional ventilation. Given this success we hope to renew interest in this method for adults with ARDS, together with concurrent use of manual recruitment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…With active expiration, the lung volume can be controlled to avoid over-extension of the lung tissue, reducing the risks of lung injuries. HFOV has been used extensively both on neonates25 and adults 2,6,27,28. HFV has attracted much research interest; a comprehensive review of this area of study can be found in Chang 3.…”
Section: Introductionmentioning
confidence: 99%
“…With active expiration, the lung volume can be controlled to avoid over-extension of the lung tissue, reducing the risks of lung injuries. HFOV has been used extensively both on neonates25 and adults 2,6,27,28. HFV has attracted much research interest; a comprehensive review of this area of study can be found in Chang 3.…”
Section: Introductionmentioning
confidence: 99%
“…HFOV is a shallow, fast mode of mechanical ventilation which can avoid the risk of lung injury associated with cyclic opening and closing of alveolar units in conventional ventilation. 16 HFOV has been successfully applied to neonates since 1981, 18 and more recently to adolescents 20 and adults. 1,6,19 HFOV results in better pulmonary outcomes than conventional mechanical ventilation for very low birth weight infants suffering with respiratory distress syndrome.…”
Section: Introductionmentioning
confidence: 99%
“…For these patients, HFOV is an effective therapeutical alternative, especially for non‐responders to conventional ventilation (4).…”
mentioning
confidence: 99%